Kajian Potensi Genangan dan Waktu Tiba Tsunami Di Kota Lhokseumawe - Ibrahim; Tursina; Syarifah Keumala Intan; Mirza Fahmi; Zairipan Jaya; Abdullah Irwansyah (Jurnal Serambi Engineering, 2024)
Lhokseumawe was one of the towns affected by the 2004 tsunami. During the last tsunami, tsunami waves arrived last on the coast of Lhokseumawe compared to the western and northern coastal areas of Aceh. Therefore, this tsunami modelling study was conducted to determine the arrival time of tsunami waves onthe coast of Lhokseumawe city and to determine the affected areas from the tsunami inundation map information. The method used is tsunami numerical modelling using the COMCOT (Cornell Multi Grid Coupled Tsunami Model) model. The earthquake source used to generate the tsunami is a 9.15 Mw earthquake of the magnitude of the 2004 earthquake, 8.0 Mw and 8.5 Mw earthquake scenarios. Bathymetric data were used to provide information on sea depth and topographic data to provide information on land elevation in the study area. Observation points were placed on the coast to record when the waves reached the coast. The maximum tsunami height occurred in Blang Mangat subdistrict with a tsunami height of 5 m and inundation distance of 1 km. The arrival time of the tsunami in Lhokseumawe town was 75-80 min after the earthquake. This information on tsunami height and arrival time can be used as preliminary information for tsunami mitigation planning and rapid response in the event of an earthquakewith tsunami potential.